Environmental Value and Pro-environmental Behavior Among Young Adults: The Mediating Role of Risk Perception and Moral Anger - Li, Xin; Liu, Zhenhui; Wuyun, Tena (Frontiers in Psychology, 2022)
This study aims to identify the relationship between students’ environmental value and pro-environmental behavior within a V-B-N framework. To conduct an empirical study, we used 558 samples collected from the online survey and adopted the partial least squares path modeling method to test the causal relationship between variables in the conceptual model. The results indicated that environmental value significantly affects pro-environmental behavior. In addition, we highlighted that risk perception and moral anger play critical chain mediating roles in the relationship between environmental value and pro-environmental behavior. This study has meaningful implications for practitioners to encourage the public’s eco-friendly behavior by suggesting ways to risk perception and stimulate individuals’ moral emotion on the environment.